Meningkatkan Kemampuan Guru dalam Melaksanakan Pembelajaran melalui Supervisi Akademik Berbasis Teknologi Informasi dan Komunikasi (TIK) di Sekolah Binaan Kecamatan Gondanglegi Kabupaten Malang - Tamyid, Tamyid (Universitas Nahdlatul Ulama Pasuruan, 2022)
The purpose of this study is to improve the ability of teachers to carry out learning through academic supervision based on information and communication technology (ICT) in the fostered schools, Gondanglegi District, Malang Regency. This is motivated by the not yet optimal ability of teachers in compiling learning tools. This research uses school action research with 3 cycles. In each cycle using 4 stages consisting of planning, action, observation and reflection. The data was obtained from the observation, recording, and class visits. The data were analyzed using a qualitative descriptive approach. The results of the study indicate that the development of academic supervision using ICT can improve the ability of teachers at the Fostered Schools of Gondanglegi District, Malang Regency in making learning tools. The average level of teacher ability in the first cycle was 65.05% which was classified as less, and increased in the second cycle to 72.14% which was classified as less and in the third cycle increasedto 86.70% in the good category.